2022
DOI: 10.1155/2022/9302403
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic Acid B Suppresses Non-Small-Cell Lung Cancer Metastasis through PKM2-Independent Metabolic Reprogramming

Abstract: Objective. Salvianolic acid B (Sal B) has been demonstrated to be a potential chemoprevention agent for several cancers. Herein, we investigated the pharmacological function of Sal B on non-small-cell lung cancer (NSCLC) metastasis. Methods. Two NSCLC cell lines (NCI-H2030 and NCI-H1650) were disposed of by 200 μM Sal B or 10 μM PKM2 agonist TEPP-46. Wound healing and transwell experiments were implemented for analyzing migratory and invasive capacities. Epithelial-to-mesenchymal transition (EMT) markers β-cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Similar effects were reported for rosmarinic acid, promoting cell migration in wound models [148,149] and presenting an inhibitory effect in cancer cells [150][151][152][153][154]. Salvianolic acids A and B are known to induce [155][156][157][158][159] as well as to delay [160][161][162] cell migration. The aglycone apigenin is also reported to promote wound healing in a variety of models [163][164][165][166][167] and to prevent cell migration in cancer cells [168][169][170][171][172][173][174].…”
Section: Discussionsupporting
confidence: 65%
“…Similar effects were reported for rosmarinic acid, promoting cell migration in wound models [148,149] and presenting an inhibitory effect in cancer cells [150][151][152][153][154]. Salvianolic acids A and B are known to induce [155][156][157][158][159] as well as to delay [160][161][162] cell migration. The aglycone apigenin is also reported to promote wound healing in a variety of models [163][164][165][166][167] and to prevent cell migration in cancer cells [168][169][170][171][172][173][174].…”
Section: Discussionsupporting
confidence: 65%
“…In addition, it can inhibit EMT and cell migration, hamper cell cycle progression, and induce autophagy and apoptosis in A549 cells [ 37 ]. In the NSCLC cell lines NCI-H2030 and NCI-H1650, salvianolic acid B can inhibit pyruvate kinase M2 (PKM2)-mediated metabolic reprogramming, downregulate the expression of the metabolic reprogramming-related genes lactate dehydrogenase A (LDHA) and glucose transporter 1 (GLUT1), and inactivate EMT (markedly reduced transcription factors β-catenin expression as well as elevated transmembrane glycoproteins E-cadherin expression), thereby attenuating the metastasis of NSCLC [ 38 ].…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…Breast cancer is the most common female cancer ( Di Modica et al, 2022 ; Zhang H. et al, 2022 ), with a mortality rate second only to that of lung cancer, especially since the International Agency for Research on Cancer recently found that the mortality rate for breast cancer has now gradually surpassed that of lung cancer ( Pearanpan et al, 2022 ; Yamashita and Kufe, 2022 ). Triple-negative breast cancer is highly malignant and difficult to treat ( Hacking et al, 2022 ; Montalvo-Castro and Salinas-Jazmín, 2022 ).…”
Section: Salvianolic Acid Bmentioning
confidence: 99%